Hypertension Risk in Rural Indonesia: Insights on Age, BMI, and Traditional Market Accessibility - Asyari, Aulya Rahmanisa Paramitha; Syawaliyah, Ainun Nimah; Maulana, Taqwa Ziyan; Sulastijah, Siti; Farida, Dany; Candrasari, Anika; Firda, Fathiyyatu Assadiy; Romadhon, Yusuf Alam (Universitas Muhammadiyah Surakarta, 2024)
Purpose: This study aims to evaluate the influence of traditional markets in rural areas and the relationship between definitive factors that influence through bivariate and multivariate statistical analysis. Methodology: This study used a cross-sectional design to analyze the effect of age, BMI, and the presence of traditional markets on blood pressure using data from visits to the Gatak District Health Center, Sukoharjo Regency (May-July 2024) with bivariate (Chi-Square) and multivariate (logistic regression) methods. Results: This study analyzed 9,639 respondents which showed that age 50 years and above (aOR = 4.647, p = 0.000), overweight/obese BMI (aOR = 1.677, p = 0.000), and the absence of a traditional market around the residence (aOR = 0.779, p = 0.004) were significantly associated with an increased risk of hypertension. This study states that traditional markets can function as a protective factor, while age and obesity increase the risk of hypertension in rural communities. Applications/Originality/Value: This study highlights the role of traditional markets as a protective factor against hypertension in rural Indonesia, which has rarely been discussed in previous studies; This study highlights the role of traditional markets as a protective factor against hypertension in rural Indonesia, a perspective rarely discussed in previous studies. It provides insights into their contribution to public health strategies and preventive measures.